2022
DOI: 10.1101/2022.01.13.476197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relative pitch representations and invariance to timbre

Abstract: Information in speech and music is often conveyed through changes in fundamental frequency (f0), the perceptual correlate of which is known as "pitch". One challenge of extracting this information is that such sounds can also vary in their spectral content due to the filtering imposed by a vocal tract or instrument body. Pitch is envisioned as invariant to spectral shape, potentially providing a solution to this challenge, but the extent and nature of this invariance remain poorly understood. We examined the e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Local frequency changes in SFS may then be more informative for harmonic sounds, whereas coarser SE cues may take over for inharmonic changes. However, a recent study tested pitch discrimination with interference of envelope variation and did not observe a mediating role of harmonicity in all conditions [26]. Instead, they only found a mediating role for very large intervals (9 st) or in the case when there was no overlap between the frequency components of the two sounds, but not for natural speech or musical instrument sounds.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Local frequency changes in SFS may then be more informative for harmonic sounds, whereas coarser SE cues may take over for inharmonic changes. However, a recent study tested pitch discrimination with interference of envelope variation and did not observe a mediating role of harmonicity in all conditions [26]. Instead, they only found a mediating role for very large intervals (9 st) or in the case when there was no overlap between the frequency components of the two sounds, but not for natural speech or musical instrument sounds.…”
Section: Discussionmentioning
confidence: 96%
“…Speculatively, it can be remarked that harmonicity plays an important role in auditory scene analysis [65][66][67]. In particular, harmonicity favors the binding of frequency components within and across sounds [26,65]. Local frequency changes in SFS may then be more informative for harmonic sounds, whereas coarser SE cues may take over for inharmonic changes.…”
Section: The Role Of Acoustic Cues In Frequency Change Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speculatively, it can be remarked that harmonicity plays an important role in auditory scene analysis [ 70 – 72 ]. In particular, harmonicity favors the binding of frequency components within and across sounds [ 29 , 70 ]. Local frequency changes in SFS may then be more informative for harmonic sounds, whereas coarser SE cues may take over for inharmonic changes.…”
Section: Discussionmentioning
confidence: 99%
“…For inharmonic sounds, recent results by McPherson and McDermott add yet additional candidate cues to try and explain pitch judgements [ 28 ]. Using a variety of tasks usually understood as involving pitch, such as pitch discrimination, melodic contour identification, or interval judgments, the authors concluded that pitch judgements were in fact based on multiple mechanisms operating concurrently, such as the computation of f 0 from SFS cues for harmonic sounds, and the tracking of SE cues for inharmonic and harmonic sounds (see also [ 29 ]). Previously, frequency-shift detectors tracking local changes in SFS cues had also been evidenced [ 30 ], providing yet another mechanism contributing to “up” or “down” pitch judgements available for harmonic and inharmonic sounds alike [ 31 ].…”
Section: Introductionmentioning
confidence: 99%